The use of technology in family farming food production: Evolution and popular knowledge - Santos, Luan Xavier; Neto, Claudino Anacleto de Andrade; Sarmento, Mayria Rufino; Pinto , Waleska Cristina de Oliveira; Costa, Francisco Eudes Almeida da (Seven Editora, 2024)
Ethnoknowledge is a concept related to the knowledge, knowledge and cultural traditions of family farming. In this context, with the emergence of the Green Revolution, there were some obstacles to the development of subsistence agriculture with innovations in technology for food production and commercialization. In emphasis, this research aims to draw conclusions about the role of technology in family farming and its impact on the Brazilian rural economy, based on a synthesis of the results obtained from the literature review. With advances in technology, small producers are experiencing difficulties in the field, which in turn are unable to produce food on a long scale. The effect of the green revolution allowed the intensive use of pesticides, agricultural machinery, genetic improvement of seeds and other purposes that favored advances in technology in agriculture. However, with these advances, the role of agricultural production technology has caused greater complexity in agricultural activities in the field with improvements in quality, quantity, food security, economy and labor. The advancement of technology caused the lack of progress in food production in family farming, with low production and devaluation in the market. In short, it is worth highlighting that the importance of ethnoknowledge for family farmers is based on recovering cultures and traditions of original peoples, emphasizing techniques and instruments that are passed on from generations to generations, such as ancestors that are used in everyday life, experiences and knowledge transmitted. from father to children. DOI:https://doi.org/10.56238/sevened2024.014-024